HUBUNGAN KEPATUHAN KONSUMSI TABLET Fe DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI : LITERATURE REVIEW - Angela Lovendra Naingalis; Sinta Inriani Olla (Jurnal Maternitas Kebidanan, 2023)
Anemia is a medical condition that occurs when the number of red blood cells or hemoglobin levels in the body decreases below normal limits. Adolescent girls are one of the groups with a high level of vulnerability to anemia, where the prevalence of anemia in Indonesia is quite high. Young women are required to take Fe tablets because they experience a menstrual cycle that comes every month. These Fe tablets are very useful in regenerating iron that has been lost due to menstruation and to fulfill Fe needs that have not been met from food. The aim of this study was to provide an overview of the relationship between adherence to consuming Fe tablets and the incidence of anemia in adolescent girls. In this research the author used the literature review method. The database used in this research uses Google Scholar 2019-2023 with the keywords used anemia, compliance, adolescent girls, fe tablet consumtion. Based on 10 articles regarding the relationship between adherence to consuming Fe tablets and the incidence of anemia, it was found that there was a significant influence between adherence to consuming Fe tablets and the incidence of anemia in adolescent girls. The conclusion from this literature review is that there is a significant influence between adherence to consuming Fe tablets on the incidence of anemia in adolescent girls.